1978
DOI: 10.1177/009365027800500402
|View full text |Cite
|
Sign up to set email alerts
|

Female Responses To Provocation After Exposure To Aggressive and Erotic Films

Abstract: Female college students were exposed to a neutral, aggressive, or erotic film. They then were either provoked or not provoked in a game situation which provided an immediate opportunity for retaliation. Both instigation and retaliation were operationalized in the delivery of noxious noise to the opponent. Benevolent behavior, operationalized in the delivery of pleasant sounds, was a response alternative to noxious noise. Physiological reactions to the films were measured These measures revealed that the erotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…In one study, exciting film clips were found to have an excitation-transfer effect on music, whereby increasingly arousing film clips led to greater liking of a rock song heard a few minutes after viewing the clip (Cantor & Zillmann, 1973). Other studies have shown the ability for physiologicallyarousing video segments to intensify emotional responses to mediated (Zillmann, Mody, & Cantor, 1974) or non-mediated stimuli (Cantor, Zillmann, & Einsiedel, 1978). In addition, increased arousal from physical exercise has resulted in higher ratings of arousal and enjoyment of later media content (Cantor, Zillmann, & Bryant, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, exciting film clips were found to have an excitation-transfer effect on music, whereby increasingly arousing film clips led to greater liking of a rock song heard a few minutes after viewing the clip (Cantor & Zillmann, 1973). Other studies have shown the ability for physiologicallyarousing video segments to intensify emotional responses to mediated (Zillmann, Mody, & Cantor, 1974) or non-mediated stimuli (Cantor, Zillmann, & Einsiedel, 1978). In addition, increased arousal from physical exercise has resulted in higher ratings of arousal and enjoyment of later media content (Cantor, Zillmann, & Bryant, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…One might argue, however, that our theoretical analysis of triggered displaced aggression appears to share general conceptual similarities with excitation transfer theory (Zillmann, 1971(Zillmann, , 1979 and that the latter theory can explain our findings. In excitation transfer theory, a provocation is combined with a manipulation of arousal such as noise, an erotic film, or physical exercise (e.g., Cantor, Zillmann, & Einsiedel, 1978;Donnerstein & Wilson, 1976;Zillmann, Katcher, & Milavsky, 1972). 4 At first glance, such manipulations of arousal correspond in some sense to what we have called a triggering event.…”
Section: The Relationship Between Ruminatively Based Displaced Aggresmentioning
confidence: 99%
“…Research on the effect of pornography on women's aggression has even less social grounding (e.g., Baron, 1979;Cantor, Zillmann, & Einsiedel, 1978), because female aggression is not a major social problem and as such has given little insight into women's experiences.…”
mentioning
confidence: 99%